Hepatic Positron Emission Tomography: Applications in Metabolism, Haemodynamics and Cancer - Honka Miikka-Juhani; Rebelos Eleni; Malaspina Simona; Nuutila Pirjo (MDPI, 2022)
Evaluating in vivo the metabolic rates of the human liver has been a challenge due to its unique perfusion system. Positron emission tomography (PET) represents the current gold standard for assessing non-invasively tissue metabolic rates in vivo. Here, we review the existing literature on the assessment of hepatic metabolism, haemodynamics and cancer with PET. The tracer mainly used in metabolic studies has been [F-18]2-fluoro-2-deoxy-D-glucose (F-18-FDG). Its application not only enables the evaluation of hepatic glucose uptake in a variety of metabolic conditions and interventions, but based on the kinetics of F-18-FDG, endogenous glucose production can also be assessed. 14(R,S)-[F-18]fluoro-6-thia-Heptadecanoic acid (F-18-FTHA), C-11-Palmitate and C-11-Acetate have also been applied for the assessment of hepatic fatty acid uptake rates (F-18-FTHA and C-11-Palmitate) and blood flow and oxidation (C-11-Acetate). Oxygen-15 labelled water (O-15-H2O) has been used for the quantification of hepatic perfusion. F-18-FDG is also the most common tracer used for hepatic cancer diagnostics, whereas C-11-Acetate has also shown some promising applications in imaging liver malignancies. The modelling approaches used to analyse PET data and also the challenges in utilizing PET in the assessment of hepatic metabolism are presented.